Emotion matters: Implications for distracted driving. (February 2015) - Chan, Michelle; Singhal, Anthony
Highlights: We examine the effects of emotion-related auditory distraction while driving. Emotional valence and arousal differentially influences driving behaviours. Negative emotional content impairs driving performance. Event-related potentials reveal a division of neural resources in dual-task. Abstract: Driver distraction is estimated to be one of the leading causes of motor vehicle accidents. Roadside billboards containing negative and positive emotional content have been shown to influence driving behaviour by modulating attention; however, the impact of emotion-related auditory distraction on driving is relatively unknown. In the present study, we explored the behavioural and event-related potential (ERP) effects elicited by auditorily presented words of different emotional valence during driving (dual-task) and non-driving (single-task) conditions. The results demonstrate that emotion-related auditory distraction can differentially affect driving performance depending on the valence of the emotional content. Negative distractions reduced lateral control and slowed driving speeds compared to positive and neutral distractions. On the other hand, the results revealed an arousal effect on memory and decision-making during driving as performance improved with both negative and positive distractions. Finally, ERPs elicited by the auditory distractions were reduced in amplitude during driving compared to non-driving, revealing a division of cognitive resources under dual-task demands. These findings have important implications for road safety and bring to light the detrimental effects of negative emotional auditory content on driving performance. Furthermore, these findings show that emotional valence and arousal can differentially influence behaviour.